MANTERA KECANTIKAN WANITA BAJAU: ANALISIS BAHASA DAN PEMIKIRAN - Abdul Ghani, Rahmah; Ahmad, Zahir; Musa Kahn, Sabzali (JURNAL MELAYU SEDUNIA, 2019)
This article discussed the language and thought analysis of mantras among Bajau women’s beauty in Sabah. The shift from animism to Islam has created a universal application of mantras. The mantras structure has been transformed according to Islam, for example, the beginning of mantras as with the recitation of Bismillahir-Rahmanir-Rahim which ends with Laila-hail-lallah. The words in mantras can stimulate the senses in human beings to become according to their through this practice. This research is qualitative and data is collected by literature review and field survey. Interview and observation were also used. The data was collected by interviewing a few informants. The mantras beauty was practiced by the Bajau women are categorized into sweetness mantras, strengthening, obedient, love and protection. In the mantras, there are words and phrases that are related to the belief of Bajau ethnic who are Moslem. The practice of mantra is associated with health care and the relationship between individuals in an institution or a society. Women who practiced mantras are seen as more confident and skillful. They are seen prettier when they use accessories and certain attire for example in a wedding ceremony. The words and phrases used in the mantras are influenced by Islam for example, names of the prophet, names of prophet’s “sahabat” and names related to the characters in the Hindu epic and panji literature. From the analysis, the thought process in the practitioner of the mantra are thoughts on religion, supernatural and cosmology aspects.